2022
DOI: 10.3389/fonc.2022.1008027
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming therapeutic resistance to platinum-based drugs by targeting Epithelial–Mesenchymal transition

Abstract: Platinum-based drugs (PBDs), including cisplatin, carboplatin, and oxaliplatin, have been widely used in clinical practice as mainstay treatments for various types of cancer. Although there is firm evidence of notable achievements with PBDs in the management of cancers, the acquisition of resistance to these agents is still a major challenge to efforts at cure. The introduction of the epithelial-mesenchymal transition (EMT) concept, a critical process during embryonic morphogenesis and carcinoma progression, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 177 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…In the synergistic phototherapy experiment in vivo , the results showed that the tumor volume of the ICG-PtMGs@HGd group under NIR irradiation decreased most significantly, and the body weight of the tumor-bearing mice did not change significantly after treatment. In general, there is a wide range of biological applications of Pt-based nanomaterials, but the toxic side effects caused by heavy metals are still current challenges to be overcome ( Duan et al, 2022 ; Velcheva et al, 2022 ).…”
Section: Nanomaterial-mediated Tumor Hypoxia Reliefmentioning
confidence: 99%
“…In the synergistic phototherapy experiment in vivo , the results showed that the tumor volume of the ICG-PtMGs@HGd group under NIR irradiation decreased most significantly, and the body weight of the tumor-bearing mice did not change significantly after treatment. In general, there is a wide range of biological applications of Pt-based nanomaterials, but the toxic side effects caused by heavy metals are still current challenges to be overcome ( Duan et al, 2022 ; Velcheva et al, 2022 ).…”
Section: Nanomaterial-mediated Tumor Hypoxia Reliefmentioning
confidence: 99%
“…Chemoresistance remains a major challenge in the management of patients with CRC. Several mechanisms of oxaliplatin resistance have been reported, including reduced cellular drug uptake and accumulation [ 26 ], increased repair of DNA damage [ 27 ], induction of epithelial-mesenchymal transition (EMT) [ 28 ], and desensitization to cell apoptosis [ 29 ]; however, effective strategies for reversing resistance have not been achieved. Emerging evidence suggests that aberrant cancer metabolism could impart drug resistance [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Development of the EMT phenotype is one of the major mechanisms that allow tumor cells to become resistant to platinum-based drug [ 223 ]. Since cisplatin is the first-line option for NPC chemotherapy, exploiting treatment to prevent or reverse EMT is of great importance.…”
Section: Strategies To Overcome Drug Resistance In Npcmentioning
confidence: 99%